Defect-Engineered Heat Transport in Graphene: A Route to High Efficient Thermal Rectification - Zhao, Weiwei (Sci Rep, 2015)
Low-dimensional materials such as graphene provide an ideal platform to probe the correlation between thermal transport and lattice defects, which could be engineered at the molecular level. In this work, we perform molecular dynamics simulations and non-contact optothermal Raman measurements to study this correlation. We find that oxygen plasma treatment could reduce the thermal conductivity of graphene significantly even at extremely low defect concentration (∼83% reduction for ∼0.1% defects), which could be attributed mainly to the creation of carbonyl pair defects. Other types of defects such as hydroxyl, epoxy groups and nano-holes demonstrate much weaker effects on the reduction where the sp(2) nature of graphene is better preserved. With the capability of selectively functionalizing graphene, we propose an asymmetric junction between graphene and defective graphene with a high thermal rectification ratio of ∼46%, as demonstrated by our molecular dynamics simulation results. Our findings provide fundamental insights into the physics of thermal transport in defective graphene, and two-dimensional materials in general, which could help on the future design of functional applications such as optothermal and electrothermal devices.